2022
DOI: 10.1007/s00520-022-06969-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of symptoms and signs in patients with advanced cancer in the last days of life: the East Asian collaborative cross-cultural study to elucidate the dying process (EASED)

Abstract: Purpose Few large-scale studies have focused on the prevalence of symptoms and signs during the last days of patients diagnosed with advanced cancer. Identifying the patterns of speci c symptoms according to cancer type is helpful to provide end-of-life care for patients with advanced cancer. We investigated the prevalence and severity of symptoms and signs associated with impending death in patients with advanced cancer. Methods In this secondary analysis of an international multicenter cohort study conducted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A recent study ( N = 2131) conducted in 38 palliative care units in three East Asian countries observed patients in the last 3 days of life. 76 The authors reported that fatigue, dry mouth, drowsiness and dyspnoea were the most frequent symptoms and lower body oedema was the most common sign as death approached. In a study of palliative cancer patients ( N = 178), ‘death rattle’ was found to be a prognostic factor for death within 48 h with a PPV of 74% and NPV of 77%; altered level of consciousness was less predictive (PPV of 64% and NPV of 67%).…”
Section: Prognosticating In Patients With An Expected Survival Of Daysmentioning
confidence: 99%
“…A recent study ( N = 2131) conducted in 38 palliative care units in three East Asian countries observed patients in the last 3 days of life. 76 The authors reported that fatigue, dry mouth, drowsiness and dyspnoea were the most frequent symptoms and lower body oedema was the most common sign as death approached. In a study of palliative cancer patients ( N = 178), ‘death rattle’ was found to be a prognostic factor for death within 48 h with a PPV of 74% and NPV of 77%; altered level of consciousness was less predictive (PPV of 64% and NPV of 67%).…”
Section: Prognosticating In Patients With An Expected Survival Of Daysmentioning
confidence: 99%
“…7 Actively dying patients with advanced cancer typically experience multiple sources of suffering and symptoms that significantly affect their quality of life, such as pain, fatigue, breathlessness, nausea, constipation, diarrhea, anxiety, depression, insomnia, and confusion. 8 In addition, cancer has been regarded as a family disease, affecting not only the patients but also their family members who are required to provide support and care, including assistance with personal care, symptom management, treatment monitoring, and emotional, financial, and spiritual support. 9 Therefore, cancer patients in their final days require careful symptom management, and families need support and coaching as death approaches.…”
Section: Introductionmentioning
confidence: 99%
“…algorithm, cancer, dyspnea, feasibility, palliative care 1 The comprehensive pharmacological treatment algorithm for terminal cancer dyspnea patients. RASS, Richmond Agitation-Sedation Scale algorithm for patients with terminal dyspnea.…”
Section: Introductionmentioning
confidence: 99%
“…Dyspnea is among the most frequent and deteriorating symptoms in the terminal phase of life of cancer patients (“terminal dyspnea”) 1–3 . Previous research indicated the efficacy of opioids as the first‐line therapy for terminal dyspnea patients 4–8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation